The potential and advances in RNAi therapy: Chemical and structural modifications of siRNA molecules and use of biocompatible nanocarriers - Joo, Min Kyung; Yhee, Ji Young; Kim, Sun Hwa; Kim, Kwangmeyung (ELSEVIER SCIENCE BV, 2014)
Small interfering RNA (siRNA) has attracted great attention as a potential new drug due to its highly sequence-specific gene silencing ability and generality in therapeutic target. However, the medical applications of siRNA have been severely hindered by the lack of an optimal systemic delivery methodology. This poor delivery performance of siRNA is mainly caused by its inherent physicochemical properties including short and stiff structure, low charge density and vulnerability to nuclease cleavage. Thus, the successful development of efficient systemic delivery platform for siRNA is a fundamental requirement necessary to bring siRNA-based drugs to the market. Herein, we describe some siRNA delivery methods based on the chemical and structural modifications of delivery materials and siRNA itself to carry siRNA therapeutics safely to the targeted place without adverse effects. This review particularly explains the latest progress of chemically and structurally modified siRNA polymer (poly-siRNA)-based delivery systems. The stable and compact siRNA polyplexes, which are formed by poly-siRNA and different types of biocompatible materials, can enhance serum stability and target delivery efficiency in vitro and in vivo. In addition, this review provides specific information on poly-siRNA delivery systems from basics to therapeutic applications in different animal disease models. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: POLYMERIZED SIRNA; CELLULAR UPTAKE; DELIVERY; GENE; INTERFERENCE; NANOPARTICLES; EFFICIENT; GELATIN; ALBUMIN; RELEASE